Chemical profile and bioaccessibility of polyphenols from wheat pasta supplemented with partially-deoiled chia flour. (April 2020) - Pigni, Natalia B.; Aranibar, Carolina; Lucini Mas, Agustín; Aguirre, Alicia; Borneo, Rafael; Wunderlin, Daniel; Baroni, M. Verónica
Abstract: The by-product obtained after the oil extraction from chia seeds has been used to produce supplemented wheat pasta, generating a food product with improved nutritional quality. In a previous work, we have demonstrated its technological feasibility, as well as its good acceptance by semi-trained judges. One of the enhanced nutritional properties of the supplemented pasta was the antioxidant capacity. In the present work, we characterize the phenolic composition of partially-deoiled chia flour and the supplemented pasta by HPLC-MS/MS. Fourteen polyphenols, mostly phenolic acids, have been identified in the acetone/water (4:1) extract. The two major components were rosmarinic acid and its glycoside (salviaflaside). The study of the effects of cooking on the phenolic profile showed that many bioactive components of chia seeds remain stable at the moment of intake. Finally, the bioaccessibility of the polyphenols has been assessed through an in vitro simulation of human gastrointestinal digestion. Highlights: Wheat pasta enriched with chia flour has shown improved antioxidant properties. The polyphenols profile of supplemented pasta has been analyzed through HPLC-MS/MS. Effects of manufacture, cooking and digestion on polyphenols has been assessed. The main bioactive compounds of chia remain stable until the moment of intake. Rosmarinic acid and salviaflaside are detected at the intestinal stage of digestion.